Impact of statin use on short- and long-term outcomes in patients with sepsis-induced myocardial injury: insights from the MIMIC-IV database - Liu, Yuan; Chen, Jijiang; Yuan, Yehao; Niu, Pingping; Wu, Mengyi; Shang, Baoling; Lu, Weihui; Zou, Xu; Yao, Gengzhen (Frontiers in Pharmacology, 2025)
BackgroundSepsis-induced myocardial injury (SIMI) is a critical complication of sepsis, marked by high mortality rates, and lacks effective treatments. The impact of statin therapy on mortality in SIMI patients remains unclear. This study aims to explore the association between statin use and mortality in SIMI patients, focusing on both short-term and long-term outcomes.MethodsA retrospective cohort study was conducted by extracting SIMI patient information from the Medical Information Mart for Intensive Care IV (MIMIC-IV) database. Patients were categorized into statin and non-statin groups. A 1:1 nearest propensity-score matching (PSM) was used to balance baseline characteristics. Survival outcomes were assessed using Kaplan-Meier analysis and robust Cox proportional hazards models to understand the effects of statin use, type and dosage on mortality at 28 days, 90 days, and 1 year. E-Value analysis was used for unmeasured confounding.ResultsA total of 2,246 patients meeting SIMI criteria were enrolled in the final cohort, with 17.9% receiving statins during their ICU stay. Statin use was associated with significantly lower mortality at all time points, as shown by Kaplan-Meier analysis. In multivariable robust Cox regression models, statin therapy correlated with a 32% reduction in 28-day mortality (HR = 0.68, 95% CI: 0.49–0.94), a 29% reduction at 90 days (HR = 0.71, 95% CI: 0.54–0.93), and a 28% reduction at 1 year (HR = 0.72, 95% CI: 0.58–0.90), maintaining significance after adjustment for confounders. Simvastatin was particularly effective, and low-dose statins were linked to reduced mortality risk. Subgroup analyses suggested consistent statin benefits. E-Value analysis suggested robustness to unmeasured confounding.ConclusionOur study demonstrates that statin use is significantly associated with reduced mortality in SIMI patients across 28 days, 90 days, and 1 year. Simvastatin provides substantial benefits, with low-dose statins providing greater advantages compared to high-dose formulations.